The Effect of Transformational Leadership Style and Work Environment on Turnover Intention Through Work Engagement - Fitri Rezeki; Yuan Badrianto (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
In the era of globalization and the increasingly dynamic development of the world of work, organizations are required to be able to manage human resources effectively to maintain business continuity. One of the main challenges in human resource management is high turnover intention, namely the tendency of employees to leave the company. This condition needs to be considered because it can have an impact on productivity, organizational stability, recruitment costs, retraining needs, and team work effectiveness. This study aims to analyze the influence of transformational leadership style and work environment on turnover intention through work engagement among employees of PT. XYZ in Bekasi. This study uses a quantitative approach with the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) analysis method through SmartPLS software. The research sample consisted of 50 respondents who were determined using the saturated sampling technique. The research variables consist of transformational leadership style and work environment as independent variables, work engagement as a mediating variable, and turnover intention as the dependent variable. Testing was conducted through the evaluation of the outer model, inner model, and hypothesis testing based on t-statistic and p-value values at a significance level of 5%. This study is expected to provide an understanding of the importance of leadership, work environment, and work engagement in reducing employee turnover intention.